Ethical Responsibility Formation of Students in a Nuclear Engineering Course Through Inquiry Learning - Ha, Minha R.; Racette, Joshua; Nagasaki, Shinya (Journal of Leadership, Accountability and Ethics, 2020)
This article presents an approach of embedding sociotechnical competency development in a traditional technical undergraduate course in an Engineering Physics program. An inquiry project was integrated into the course and served as the main evidence of the students’ demonstrated ability to integrate social, ethical, and technical analyses. Surveys were administered to collect feedback and student perspectives on their learning outcomes and the impact of the course components. Results from 2017-2019 were analyzed to examine the possible mechanisms and principles by which particular course components contributed to enhancing ethical responsibility, and how ethical responsibility is conceptualized for the nuclear industry context